Eutanasia dalam Perspektif Masā’il Fiqhiyyah - Muhammad Alfin Asy-Syakuuri; Zulfa Nurfaidah; Astri Nur Asfiah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Current advances in the medical world have opened up opportunities for people to extend their lives thanks to various innovative health technologies. However, on the other hand, this has also encouraged the emergence of euthanasia as a means to alleviate suffering in terminally ill patients. Euthanasia is a highly debated topic, particularly within Islamic law, as it relates to the right to life and the prohibition of actions that take life. This study aims to explore the definition of euthanasia, its types, and the laws governing its implementation from the perspective of Masā'il Fiqhiyyah. This study adopted a qualitative method with a normative approach through a literature analysis of both classical and contemporary fiqh sources, as well as fatwas issued by Islamic institutions. The research findings indicate that active euthanasia is generally considered haram (forbidden) because it is an act that directly takes life. Meanwhile, passive euthanasia remains a topic of debate among Islamic scholars, particularly in certain situations, such as discontinuing treatment that offers no prospect of recovery. In the context of Islamic jurisprudence (Masā'il Fiqhiyyah), determining the law regarding euthanasia takes into account the maqasid of sharia, particularly in protecting the soul (ḥifẓ al-nafs), as well as the principles of Islamic jurisprudence that emphasize the need to prevent harm rather than achieve benefit. Therefore, the study of euthanasia in Islam requires a comprehensive ijtihad approach to provide solutions to the challenges of modern medicine without neglecting Sharia principles. Keywords: Euthanasia, Contemporary Fiqh, Masā’il Fiqhiyyah, Maqashid Sharia